Constraining the Age of Floodplain Levels Along the Lower Section of River Tisza, Hungary - Sipos, György; Kiss, Tímea; Tóth, Orsolya (Journal of Environmental Geography, 2016)
During the Late Pelistocene-Holocene transition the fluvial landscape of the Great Hungarian Plain changed considerably as a consequence of tectonic, climatic and geomorphological factors. Geochronology, and especially luminescence dating, is a very important tool in reconstructing these changes. The present study focuses on the Lower-Tisza region and addresses the timing of the development of different floodplain levels. In the meantime the luminescence characteristics of the investigated alluvial sediments were also assessed, with a special emphasis on the comparison of silty fine grain and sandy coarse grain results, as in the given medium and low energy environment fine grain sediments are more abundant, however, based on the literature, coarse grain samples are more reliable in terms of luminescence dating. Measurements were performed on 12 samples originating from the point bars of two large palaeo-meanders, representing different floodplain levels along the river. Results indicate the applicability of both grain size fractions for dating purposes, though fine grain subsamples overestimate in average by 1.5 ka the ages yielded by coarse grain subsamples. Consequently, fine grain samples can be used for outlining only general trends, and results need to be controlled by coarse grain measurements where possible. Based on the ages received, the upper floodplain was actively formed until 13-15 ka, when incision and the development of an intermediate floodplain level started. The meander on the intermediate flood plain level developed then very actively until 9 ka. As indicated by the received age information the intensity of meander formation could be highly affected by climatic and especially vegetation control. However, reconstruction can be refined later by further sampling and the application of the results of the present paper.